Increase in child behavior problems among urban Brazilian 4‐year olds: 1993 and 2004 Pelotas birth cohorts. (16th April 2014) - Matijasevich, Alicia; Murray, Elizabeth; Stein, Alan; Anselmi, Luciana; Menezes, Ana M.; Santos, Iná S.; Barros, Aluísio J.D.; Gigante, Denise P.; Barros, Fernando C.; Victora, Cesar G.
<x xml:space="preserve">Abstract</x> Background There are an increasing number of reports on time trends in child and adolescent psychological problems but none from low‐ and middle‐income countries, and very few covering the preschool period. The aim was to investigate changes in preschool behavioral/emotional problems in two birth cohorts from a middle‐income country born 11 years apart. Methods We analyzed data from the 1993 and 2004 Pelotas birth cohort studies from Brazil. A subsample of 4‐year olds from the 1993 cohort (634) and all 4‐year olds from the 2004 cohort (3750) were assessed for behavioral/emotional problems through maternal report using the Child Behavior Checklist (CBCL). Response rates in these two population‐based cohorts were above 90%. Results We found a significant increase in CBCL total problems, internalizing and externalizing mean scores over the 11‐year period. For 1993 and 2004 Pelotas cohorts, respectively, CBCL mean values (SE) total problems scores were 27.9 (0.8) and 34.7 (0.3); for internalizing scores, 5.7 (0.2) and 6.3 (0.1) and for externalizing scores, 12.4 (0.4) and 15.5 (0.1). After adjusting for confounding variables, the largest increase from 1993 to 2004 was identified in the aggressive behavior syndrome score (Cohen's d = .50), followed by the externalizing problem score (Cohen's d = .40) and CBCL total problem score (Cohen's d = .36), respectively. The rise in child psychological problems was more marked in children from families with fewer assets and with less educated mothers. Conclusions Our findings provide evidence for a substantial increase in preschool behavioral problems among children in Brazil over an 11‐year period.